Foreign body in gallbladder: A case report (Indian Journal of Case Reports, 2020)
Foreign bodies in the gall bladder are a rare event, and they being asymptomatic is even rarer. The rarity of such a clinical entity makes the following worthwhile of recording. We report the case of a 51-year-old male who was incidentally found to have gallstones on abdominal ultrasound. The patient himself was asymptomatic. Blood investigations were unremarkable. The patient underwent a laparoscopic cholecystectomy which was later converted to an open procedure. Intraoperatively, he was found to have a cholecystoduodenal fistula for which cholecystectomy, resection of fistula, and repair of the duodenum were done. On bisecting the gallbladder specimen, it was found to contain a wooden toothpick. To the best of our knowledge, this is the first report in the medical literature of a toothpick inside the gallbladder.